2000
DOI: 10.1126/science.288.5468.1062
|View full text |Cite
|
Sign up to set email alerts
|

A High-Affinity Iron Permease Essential for Candida albicans Virulence

Abstract: Microbial pathogens must compete with the iron-withholding defense systems of their host to acquire this essential nutrient. Here, two high-affinity iron permease genes, CaFTR1 and CaFTR2, were isolated. CaFTR1 expression was induced under iron-limited conditions and repressed when iron supply was sufficient, whereas the expression of CaFTR2 was regulated in a reversed manner. Mutants lacking CaFTR1 but not CaFTR2 exhibited a severe growth defect in iron-deficient medium and were unable to establish systemic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
360
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(379 citation statements)
references
References 21 publications
15
360
1
3
Order By: Relevance
“…Iron uptake has been shown to be important for virulence in C. albicans and it has been demonstrated that a homozygous Caftr1-null mutant is unable to establish a systemic infection in a mouse model (Ramanan & Wang, 2000). In S. cerevisiae, it has been observed that deletions in genes that facilitate high-affinity copper uptake or delivery of copper ions to the multicopper oxidase ScFet3p result in strains that also display defective high-affinity iron uptake (Knight et al, 1996;Lin et al, 1997;Yuan et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron uptake has been shown to be important for virulence in C. albicans and it has been demonstrated that a homozygous Caftr1-null mutant is unable to establish a systemic infection in a mouse model (Ramanan & Wang, 2000). In S. cerevisiae, it has been observed that deletions in genes that facilitate high-affinity copper uptake or delivery of copper ions to the multicopper oxidase ScFet3p result in strains that also display defective high-affinity iron uptake (Knight et al, 1996;Lin et al, 1997;Yuan et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…It has now been identified that this is also the case for the fungal pathogen Candida albicans (Ramanan & Wang, 2000). Iron acquisition presents a particular problem to pathogenic micro-organisms due to the hostile environment of the human host.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two genes, CFL1 (Hammacott et al, 2000) and RBT2 encode functional surface ferrireductases homologous to the S. cerevisiae Fre family. CaFET3, a multicopper oxidase gene involved in high-affinity ferrous transport, was recently cloned (Eck et al, 1999), and the high-affinity iron permease CaFTR1 was shown to be required for C. albicans virulence (Ramanan and Wang, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a system of low-affinity iron uptake seems to occur in P. brasiliensis, as inferred from the expression of ferric reductase and low-affinity iron transport permease ). In C. albicans there are two genes encoding iron permease and the high affinity transporter is required for virulence in a mouse model of infection (Ramanan & Wang 2000).…”
Section: The Most Prominent Metabolic Pathways Induced During the Dimmentioning
confidence: 99%